Warm Arctic-cold continents: climate impacts of the newly open Arctic Sea - Overland, James E.; Wood, Kevin R.; Wang, Muyin (Polar research, 2011)
Recent Arctic changes are likely due to coupled Arctic amplification mechanisms with increased linkage between Arctic climate and sub-Arctic weather. Historically, sea ice grew rapidly in autumn, a strong negative radiative feedback. But increased sea-ice mobility, loss of multi-year sea ice, enhanced heat storage in newly sea ice-free ocean areas, and modified wind fields form connected positive feedback processes. One-way shifts in the Arctic system are sensitive to the combination of episodic intrinsic atmospheric and ocean variability and persistent increasing greenhouse gases. Winter 2009/10 and December 2010 showed a unique connectivity between the Arctic and more southern weather patterns when the typical polar vortex was replaced by high geopotential heights over the central Arctic and low heights over mid-latitudes that resulted in record snow and low temperatures, a warm Arctic-cold continents pattern. The negative value of the winter (DJF 2009/10) North Atlantic Oscillation (NAO) index associated with enhanced meridional winds was the lowest observed value since the beginning of the record in 1865. Wind patterns in December 2007 and 2008 also show an impact of warmer Arctic temperatures. A tendency for higher geopotential heights over the Arctic and enhanced meridional winds are physically consistent with continued loss of sea ice over the next 40 years. A major challenge is to understand the interaction of Arctic changes with climate patterns such as the NAO, Pacific North American and El Niño-Southern Oscillation.